Predicting Downward Longwave Radiation for Various Land Use in All-Sky Condition: Northeast Florida - Chi-Han Cheng; Fidelia Nnadi (Advances in Meteorology)
Accurate estimate of the surface longwave radiation is important for the surface radiation budget, which in turn controls evaporation and sensible heat fluxes. Regional land use changes can impact local weather conditions; for example, heterogeneous land use patterns and temporal changes in atmospheric circulation patterns would affect air temperature and water vapor pressure, which are more commonly used as inputs in existing models for estimating downward longwave radiation (LWd). In this study, first, we analyzed the cloud cover and land use covers impacts on LWd. Next, LWd on all-sky conditions were developed by using the existing land use-adapted model and cloud cover data from the region of Saint Johns River Water Management District (SJRWMD), FL. The results show that factors, such as, seasonal effects, cloud cover, and land use, are of importance in the estimation of LWd and they cannot be ignored when developing a model for LWd prediction. The all-sky land use-adapted model with all factors taken into account performs better than other existing models statistically. The results of the statistical analyses indicated that the BIAS, RMSE, MAE, and PMRE are −0.18 Wm−2, 10.81 Wm−2, 8.00 Wm−2, and 2.30%; −2.61 Wm−2, 14.45 Wm−2, 10.64 Wm−2, and 3.19%; −0.07 Wm−2, 10.53 Wm−2, 8.03 Wm−2, and 2.27%; and −0.62 Wm−2, 13.97 Wm−2, 9.76 Wm−2, and 2.87% for urban, rangeland, agricultural, and wetland areas, respectively.